Serie "Unser Zeichen ist die Sonne", no. 2. Pressekonferenz nach der Rückkehr vom "Friedensflug nach Osten" (1947)
Serie "Unser Zeichen ist die Sonne", no. 2. Pressekonferenz nach der Rückkehr vom "Friedensflug nach Osten".